Liquid export of Arctic freshwater components through the Fram Strait 1998–2011 - G. Kattner; A. Beszczynska-Möller; A. Mackensen; U. Schauer; E. Hansen; E. Falck; P. A. Dodd; B. Rabe; E. J. Rohling; K. Cox (Ocean Science, 2013)
We estimated the magnitude and composition of southward liquid freshwater transports in the East Greenland Current near 79° N in the Western Fram Strait between 1998 and 2011. Previous studies have found this region to be an important pathway for liquid freshwater export from the Arctic Ocean to the Nordic Seas and the North Atlantic subpolar gyre. Our transport estimates are based on six hydrographic surveys between June and September and concurrent data from moored current meters. We combined concentrations of liquid freshwater, meteoric water (river water and precipitation), sea ice melt and brine from sea ice formation, and Pacific Water, presented in Dodd et al. (2012), with volume transport estimates from an inverse model. The average of the monthly snapshots of southward liquid freshwater transports between 10.6° W and 4° E is 100 ± 23 mSv (3160 ± 730 km3 yr−1), relative to a salinity of 34.9. This liquid freshwater transport consists of about 130% water from rivers and precipitation (meteoric water), 30% freshwater from the Pacific, and −60% (freshwater deficit) due to a mixture of sea ice melt and brine from sea ice formation. Pacific Water transports showed the highest variation in time, effectively vanishing in some of the surveys. Comparison of our results to the literature indicates that this was due to atmospherically driven variability in the advection of Pacific Water along different pathways through the Arctic Ocean. Variations in most liquid freshwater component transports appear to have been most strongly influenced by changes in the advection of these water masses to the Fram Strait. However, the local dynamics represented by the volume transports influenced the liquid freshwater component transports in individual years, in particular those of sea ice melt and brine from sea ice formation. Our results show a similar ratio of the transports of meteoric water and net sea ice melt as previous studies. However, we observed a significant increase in this ratio between the surveys in 1998 and in 2009. This can be attributed to higher concentrations of sea ice melt in 2009 that may have been due to enhanced advection of freshwater from the Beaufort Gyre to the Fram Strait. Known trends and variability in the Arctic liquid freshwater inflow from rivers are not likely to have had a significant influence on the variation of liquid freshwater component transports between our surveys. On the other hand, known freshwater inflow variability from the Pacific could have caused some of the variation we observed in the Fram Strait. The apparent absence of a trend in southward liquid freshwater transports through the Fram Strait and recent evidence of an increase in liquid freshwater storage in the Arctic Ocean raise the question: how fast will the accumulated liquid freshwater be exported from the Arctic Ocean to the deep water formation regions in the North Atlantic and will an increased export occur through the Fram Strait.